2006
DOI: 10.1002/jcb.20778
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of human mesenchymal stem cells that maintain osteochondral fates

Abstract: Adult stem cells are essential for tissue renewal, regeneration and repair, and their expansion in defined culture medium is on focus for regenerative medicine and genetic pathologies. The bone marrow has been shown to be very rich is pluripotent mesenchymal stem cells (MSCs) capable of forming bone, cartilage and also may give rise, to neurons and astrocytes in vivo and in vitro. MSCs can be isolated and expanded in culture, but human cells cannot be verified for a cartilage or a bone fate by transfer experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 50 publications
3
28
0
Order By: Relevance
“…The characteristics of the same batches of hMSCs used here have been reported in previous studies (31) and confirmed by internal control experiments showing the appearance of osteocytic and chondriocytic phenotypes in response to standard protocols (31). The mRNA and protein of the GLP-1R were identified in hMSCs, which is consistent with the actions of its agonists on the processes we have described.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The characteristics of the same batches of hMSCs used here have been reported in previous studies (31) and confirmed by internal control experiments showing the appearance of osteocytic and chondriocytic phenotypes in response to standard protocols (31). The mRNA and protein of the GLP-1R were identified in hMSCs, which is consistent with the actions of its agonists on the processes we have described.…”
Section: Discussionsupporting
confidence: 73%
“…All procedures were carried out according to the Declaration of Helsinki II after permission had been obtained from the Hospital Universitario La Princesa Ethics Committee together with the volunteers' consent. The isolation and expansion of hMSCs from 36 healthy donors (between 24 and 52 yr old) were carried out as described previously (31). Cells were grown in a standard culture medium consisting of Dulbecco's modified Eagle's medium-low glucose (DMEM-LG; Life Technologies), 15% fetal bovine serum (FBS) from selected batches (Hyclone, Madrid, Spain), 100 U/ml penicillin, 100 mg/ml streptomycin, and 2 mM glutamine (BioWhittaker, Madrid, Spain) at 37°C and 5% CO 2.…”
Section: Methodsmentioning
confidence: 99%
“…High TIPT insertion in the hybrid films (PEG60) induced a fibroblastic-like morphology with the characteristics described in proliferating cells. [8] We observe slightly Y-shaped cells with a homogeneous distribution on the surface. In parallel, a huge increase in cell density is observed with respect to the pure PEG film.…”
Section: Cell Behaviormentioning
confidence: 79%
“…After cell culture, samples were processed as previously described [24,25]. Briefly, the monolithic ceramic microsystems were rinsed twice with ice-cold PBS and fixed in 3.7% formaldehyde in PBS for 30 min at room temperature (RT), then washed and in PBS and either used or kept at 4°C.…”
Section: Immunofluorescencementioning
confidence: 99%